External Quality Assessment of Platelet Disorder Investigations: Results of International Surveys on Diagnostic Tests for Dense Granule Deficiency and Platelet Aggregometry Interpretation - Hayward, Catherine P.M.; Moffat, Karen A.; Plumhoff, Elizabeth; Timleck, Marnie; Hoffman, Suzanne; Spitzer, Ernie; Van Cott, Elizabeth M.; Meijer, Piet (Seminars in Thrombosis and Hemostasis, 2012)
The quality of platelet aggregation and dense granule deficiency testing is important for diagnosing platelet function disorders. After a successful pilot exercise on diagnosing platelet dense granule deficiency by electron microscopy (EM), the North American Specialized Coagulation Laboratory Association (NASCOLA) has launched regular external quality assurance (EQA) for dense granule EM, as well as for the interpretation of platelet aggregation findings. EQA records were analyzed to assess performance. For EM EQA, between 2009 and 2011, there was excellent performance in distinguishing normal from dense granule-deficient samples and good (>70%) agreement on classifying most electron dense structures in platelets. For aggregation EQA, some normal variants were misclassified and overall case interpretations were more acceptable for rare disorders than for common findings. NASCOLA experiences with these EQAs indicate that there is a need to improve the quality of platelet disorder evaluations. For aggregometry interpretations, deficits in performance could be addressed by translating guideline recommendations into practice.
Keywords: platelet disorders; dense granule deficiency; light transmission platelet aggregometry; electron microscopy; external quality assurance